2017
DOI: 10.1161/jaha.117.007159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Insulin Signaling Regulates Glycolysis Through Phosphofructokinase 2 Content and Activity

Abstract: BackgroundThe healthy heart has a dynamic capacity to respond and adapt to changes in nutrient availability. Diabetes mellitus disrupts this metabolic flexibility and promotes cardiomyopathy through mechanisms that are not completely understood. Phosphofructokinase 2 (PFK‐2) is a primary regulator of cardiac glycolysis and substrate selection, yet its regulation under normal and pathological conditions is unknown. This study was undertaken to determine how changes in insulin signaling affect PFK‐2 content, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 52 publications
(87 reference statements)
3
37
0
Order By: Relevance
“…GK mainly expressed in hepatocytes had effects on regulating blood glucose level in vivo [ 38 ]. Previous study also found that the ability of glucose metabolism in T2DM was reduced when the syntheses of PFK and PK were decreased [ 39 ]. In this work, owing to the amelioration of the insulin signaling pathway, PEPCK, FBPase, G6Pase, and GP activities were notably decreased, while prominent increased activities of GK, PFK, PK, and GS were detected after treatment.…”
Section: Discussionmentioning
confidence: 96%
“…GK mainly expressed in hepatocytes had effects on regulating blood glucose level in vivo [ 38 ]. Previous study also found that the ability of glucose metabolism in T2DM was reduced when the syntheses of PFK and PK were decreased [ 39 ]. In this work, owing to the amelioration of the insulin signaling pathway, PEPCK, FBPase, G6Pase, and GP activities were notably decreased, while prominent increased activities of GK, PFK, PK, and GS were detected after treatment.…”
Section: Discussionmentioning
confidence: 96%
“… 322 , 325 These metabolic changes seem to be the product of higher circulating fatty acids and ketone bodies, increased fatty acid transport, decreased insulin sensitivity, downregulation of glucose transporters, elevated levels of PDK4, higher malonyl-CoA decarboxylase activity, and lower acetyl CoA carboxylase and PFK activities. 20 , 322 , 326 329 Associated with the metabolic phenotype of the diabetic heart are metabolic inflexibility, lipotoxicity (eg, accumulation of triacylglycerols, diacylglycerols, ceramide, long chain acyl CoAs, acylcarnitines), glucotoxicity, mitochondrial dysfunction, and cardiac insulin resistance. 20 , 330 , 331 …”
Section: Role Of Metabolism In Pathological Cardiac Remodelingmentioning
confidence: 99%
“…This facilitates the metabolism of glucose, taken up by GLUT4, through glycolysis. In our own work, we have found that PFK-2 content is regulated by insulin signaling and that it is constitutively decreased in mouse models of diabetes 27 . Regulation of PFK-2 content by insulin may serve as a mechanism to decrease cardiac glucose uptake and metabolism during fasting, but, in the context of diabetes, a chronic decrease in PFK-2 may contribute to metabolic inflexibility.…”
Section: Regulation Of Glucose Uptake and Metabolism In The Heartmentioning
confidence: 90%